The gut microbiota–brain axis in neurological disorder - Ullah, Hanif; Arbab, Safia; Tian, Yali; Liu, Chang-qing; Chen, Yuwen; Qijie, Li; Khan, Muhammad Inayat Ullah; Hassan, Inam Ul; Li, Ka (Frontiers in Neuroscience, 2023)
The gut microbiota (GM) plays an important role in the physiology and pathology of the host. Microbiota communicate with different organs of the organism by synthesizing hormones and regulating body activity. The interaction of the central nervous system (CNS) and gut signaling pathways includes chemical, neural immune and endocrine routes. Alteration or dysbiosis in the gut microbiota leads to different gastrointestinal tract disorders that ultimately impact host physiology because of the abnormal microbial metabolites that stimulate and trigger different physiologic reactions in the host body. Intestinal dysbiosis leads to a change in the bidirectional relationship between the CNS and GM, which is linked to the pathogenesis of neurodevelopmental and neurological disorders. Increasing preclinical and clinical studies/evidence indicate that gut microbes are a possible susceptibility factor for the progression of neurological disorders, including Alzheimer’s disease (AD), Parkinson’s disease (PD), multiple sclerosis (MS) and autism spectrum disorder (ASD). In this review, we discuss the crucial connection between the gut microbiota and the central nervous system, the signaling pathways of multiple biological systems and the contribution of gut microbiota-related neurological disorders.